2006
DOI: 10.1038/sj.emboj.7601009
|View full text |Cite
|
Sign up to set email alerts
|

Progressively impaired proteasomal capacity during terminal plasma cell differentiation

Abstract: After few days of intense immunoglobulin (Ig) secretion, most plasma cells undergo apoptosis, thus ending the humoral immune response. We asked whether intrinsic factors link plasma cell lifespan to Ig secretion. Here we show that in the late phases of plasmacytic differentiation, when antibody production becomes maximal, proteasomal activity decreases. The excessive load for the reduced proteolytic capacity correlates with accumulation of polyubiquitinated proteins, stabilization of endogenous proteasomal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
169
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(179 citation statements)
references
References 58 publications
8
169
1
1
Order By: Relevance
“…It had been noted early on that they disappear from secondary lymphoid organs when immune reactions are finished,3, 4 an observation leading Astrid Fagraeus to state that the plasma cell is “a cell which has already passed its greatest functional activity” 3. A second observation apparently supported this view, in that plasma cells isolated from secondary lymphoid organs died rapidly in cell culture, unlike other lymphocytes 5, 6, 7, 8. The apparently short lifespan of plasma cells created a conceptual problem, namely how to explain the persistence of specific antibody titers in the blood, long after termination of an immune response 9.…”
Section: Memory Plasma Cellsmentioning
confidence: 97%
“…It had been noted early on that they disappear from secondary lymphoid organs when immune reactions are finished,3, 4 an observation leading Astrid Fagraeus to state that the plasma cell is “a cell which has already passed its greatest functional activity” 3. A second observation apparently supported this view, in that plasma cells isolated from secondary lymphoid organs died rapidly in cell culture, unlike other lymphocytes 5, 6, 7, 8. The apparently short lifespan of plasma cells created a conceptual problem, namely how to explain the persistence of specific antibody titers in the blood, long after termination of an immune response 9.…”
Section: Memory Plasma Cellsmentioning
confidence: 97%
“…18 Of particular interest is the recent observation that terminally differentiated immunoglobulin (Ig)-secreting plasma cells would have impaired proteasome activity. 19 The reduced proteolytic capacity is accompanied by accumulation of polyubiquitinated proteins, stabilization of substrates such as Ik-Ba and Bax, apoptosis induction and sensitization to proteasome inhibitors. This effect has been suggested to help control plasma cell lifespan and Ig production.…”
Section: Mechanisms Of Anticancer Activity Of Proteasome Inhibitorsmentioning
confidence: 99%
“…Recently, Pengo et al have shown that autophagy indeed plays a role in dampening the antibody production, while paradoxically improving antibody yields [39]. In fact, autophagy protects "overzealous" antibodysecreting cells from a premature death caused by the proapoptotic effects of ER overload [39,40]. In support of a physiological need for curtailing μs through RIDD, a cursory BLAST search that we performed for this Commentary suggests that the μs "splice site" along with substantial stretches of flanking nucleotides is conserved in mammals.…”
Section: See Accompanying Article By Benhamron Et Almentioning
confidence: 99%
“…B-cell activation has at least three direct consequences (top right): (i) Blimp1 is upregulated, orchestrating the reprogramming of the B cell to become a plasma cell; Blimp1 represses Pax5/BSAP, leading to increased XBP-1 expression [20]; (ii) initial ER expansion is triggered in anticipation of bulk antibody production [2,43] as part of the developmental program; (iii) at a later stage massive amounts of μs are produced which activate IRE1α-dependent XBP-1 splicing and XBP-1-s protein, further driving ER expansion. This feed-forward cycle ensures massive antibody production and limits plasma-cell life span [40]. RIDD may play a role in fine-tuning μs levels vis-à-vis the protein folding capacity in the ER, ultimately safeguarding full-gear antibody production [39].…”
mentioning
confidence: 99%